Regional Climate Change and Variability 2006
DOI: 10.4337/9781781007501.00006
|View full text |Cite
|
Sign up to set email alerts
|

Foreword by Joel Scheraga

Abstract: Climate change is real. The climate has changed, is changing, and will continue to change, regardless of any human influence. But since the Industrial Revolution, human activities have begun to significantly affect the Earth's atmosphere and climate, and the changes are expected to continue for the foreseeable future. Although the timing and magnitude of future climate change is uncertain, it will have consequences for human health, ecosystems, economic activity and social well-being. Some of the effects will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Although their frequency numbers are based on six different proteins, the frequencies are qualitatively similar to those reported earlier [15]. A test of the usefulness of bend predictions of this type [15] has been made on the cytochrome c family of proteins; it was difficult to assign the positions of bends even when the bend prediction profiles of homologous sequences were used [78]. However, these bend positions, predicted by the nonamer algorithm developed here, are the only predicted bends that do persist throughout all the cytochrome c sequences.…”
Section: {J-structures and Bendssupporting
confidence: 53%
“…Although their frequency numbers are based on six different proteins, the frequencies are qualitatively similar to those reported earlier [15]. A test of the usefulness of bend predictions of this type [15] has been made on the cytochrome c family of proteins; it was difficult to assign the positions of bends even when the bend prediction profiles of homologous sequences were used [78]. However, these bend positions, predicted by the nonamer algorithm developed here, are the only predicted bends that do persist throughout all the cytochrome c sequences.…”
Section: {J-structures and Bendssupporting
confidence: 53%
“…In the case of small, highly flexible peptides it is expected that the environmental conditions play a major role in defining the preferred conformations (32,33). Conformational studies on a series of small linear peptides, however, have shown that a reasonably good agreement can be found between the computed low-energy conformations of these peptides and the experimentally determined ones (34)(35)(36)(37)(38)(39). Within this frame, we decided to explore the conformational preference of the 7-residue N-terminal portion, NH2-Glu-Val-Val-Pro-His-Lys-Lys, of the peptide antigen.…”
mentioning
confidence: 75%
“…The calculated values of J(NH -C"H) are in excellent agreement with the values measured in water at acidic pH (22-24). The differences between the mean values of J ( N H -F H ) , corresponding to the two sets of energy parameters used (8,13), are of the order of 10%.…”
Section: Resultsmentioning
confidence: 99%